1999
DOI: 10.1191/095968399674919303
|View full text |Cite
|
Sign up to set email alerts
|

The role of fire in the carbon dynamics of a mire, eastern Finland

Abstract: The fire history and the effect of fires on the long-term (apparent) rate of carbon accumulation (LORCA) in the Patvinsuo mire complex, eastern Finland, were determined through stratigraphic and pollen analyses of 98 peat cores. The peat cores were characterized by a large number of charcoal layers and the age of the basal peat varied between 57 and 10 500 years. Mire fires slowed down the progress of vertical peat accumulation and resulted in great carbon losses. The average LORCA in the Patvinsuo cores was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 35 publications
4
55
0
2
Order By: Relevance
“…Roderfelt et al (1994) have measured carbon accumulation of 64 g C m -2 yr -1 on a mire regeneration site and Tuittila et al (1999) 64.5 g CO 2 -C m -2 yr -1 in early stages of mire regeneration. These rates are quite similar to the recent apparent rate of carbon accumulation (RERCA) in Finnish natural mires, ranging from 40 to 81 g C m -2 yr -1 (Tolonen & Turunen,1996a, Pitkänen et al 1999. The dry mass accumulation of a regrowth layer in a North-American mire ranges from 120 -430 g m -2 yr -1 (Tolonen et al, 1985).…”
Section: Introductionsupporting
confidence: 60%
“…Roderfelt et al (1994) have measured carbon accumulation of 64 g C m -2 yr -1 on a mire regeneration site and Tuittila et al (1999) 64.5 g CO 2 -C m -2 yr -1 in early stages of mire regeneration. These rates are quite similar to the recent apparent rate of carbon accumulation (RERCA) in Finnish natural mires, ranging from 40 to 81 g C m -2 yr -1 (Tolonen & Turunen,1996a, Pitkänen et al 1999. The dry mass accumulation of a regrowth layer in a North-American mire ranges from 120 -430 g m -2 yr -1 (Tolonen et al, 1985).…”
Section: Introductionsupporting
confidence: 60%
“…Similar to Pitkänen et al (1999), they reported H 2 O, CO, and CO 2 as the principal gases evolved plus m/z = 32 (possibly methanol). Lopez-Capel et al (2006a) heated degraded wheat straw in a TG-DSC system (synthetic air) and recorded evolved gases using MS (temporal resolution 10 s or 3°C) and IRMS (six selected intervals over the whole combustion process each accumulating sample over 50-100 s).…”
Section: Evolved Gas Analysismentioning
confidence: 64%
“…Structural identification of evolved compounds is more conclusive with MS systems but also limited when isomers are formed or released. Pitkänen et al (1999) used TG-FTIR for identification of gaseous reaction products from the combustion (in synthetic air) of coal, peat, and plant tissue. In addition to CO 2 , CO, and H 2 O, they identified trace amounts of several low-molecular organic compounds.…”
Section: Evolved Gas Analysismentioning
confidence: 99%
“…Fire occurrence is projected to increase in boreal regions over the next century (Pitk€ anen et al, 1999;Bergeron et al, 2010). Frequent or more severe fire events could lead to a decline in carbon accumulation (Kuhry, 1994;Pitk€ anen et al, 1999;Wieder et al, 2009), though van Bellen et al (2012 did not find a clear correlation between Holocene peatland fire regimes and carbon accumulation in Qu ebec.…”
Section: Introductionmentioning
confidence: 95%